A Decade with Dötz Benzannulation in the Synthesis of Natural Products - Fernandes, Rodney A.; Kumari, Anupama; Pathare, Ramdas S. (Synlett, 2020)
The Dötz benzannulation is a named reaction that utilizes Fischer chromium carbenes in a formal [3+2+1] cycloaddition with an alkyne and CO to produce the corresponding benzannulated product. Since its development in the 1970s, this reaction has been extensively used in the synthesis of natural products and various molecular architectures. Although the reaction sometimes suffers from the formation of other competing side products, the rapid construction of naphthol structures with a 1,4-dihydroxy unit makes it the most appropriate reaction for the synthesis of p-naphthoquinones. This review focuses on our group’s efforts over the past decade on the extensive use of this annulation reaction along with the contributions of others on the synthesis of different natural products.1 Introduction2 General Description and Mechanism of the Dötz Benzannulation Reaction3 Applications of the Dötz Benzannulation in Natural Product Synthesis over the Last Decade4 Conclusion
Keywords: Dötz benzannulation; natural products; cycloaddition; Fischer carbenes; naphthoquinones